Effect of Meteorological and Hydrological Drought Changes on Vegetation NDVI in Inner Mongolia Section of Yellow River Basin - LU Jiaqi; MENG Fanhao; LUO Min; CHEN Hongguang (Renmin Zhujiang)
Under the influence of global warming and human activities, drought events in the Inner Mongolia section of the Yellow River Basin have increased in number and intensity, affecting the regional vegetation growth through the hydrological cycle and destroying ecological balance. Based on the standardized precipitation evapotranspiration index (SPEI) dataset, terrestrial water storage data, and normalized vegetation index (NDVI) data, this paper analyzes the spatial and temporal changes of meteorological droughts (SPEI) and hydrological droughts (SWSI) in the Inner Mongolia section of the Yellow River Basin during 2003—2019 and investigates their impacts on vegetation growth. The results indicate that the meteorological drought in the study area shows a decreasing trend (0.012 3/a), while the hydrological drought shows an increasing trend (0.02/a), both of which feature long duration and a high drought intensity in the study area of Bayannur city; the vegetation NDVI as a whole show a significant increasing trend (0.002 9/a), and obvious vegetation degradation appeared in some parts of Bayannur city and Hohhot city only. SPEI and NDVI are significantly positively correlated in 22.65% of the area; SWSI and NDVI are significantly positively correlated in 43.63% of the area; SPEI, SWSI, and NDVI are significantly negatively correlated mainly in the western part of Bayannur City. The effect of drought on vegetation is hysteretic; meteorological drought and hydrological drought are concentrated in January, October, and January, respectively, and the vegetation in most areas is affected more by hydrological drought in the short term.